COMPLEX REGIONAL PAIN SYNDROME: LITERATURE REVIEW AS A GUIDE FOR THE PRACTICING CLINICIAN - Dubljanin Raspopović, Emilija; Tulic, Goran; Nedeljkovic, Una; Ilic, Nela; Aleksic, Milica; Kadija, Marko; Tomanovic Vujadinovic, Sanja (Srpski medicinski časopis Lekarske komore, 2022)
Complex regional pain syndrome (CRPS) is a chronic complex disorder that significantly affects the quality of life of the people suffering from it. This syndrome affects the extremities after trauma or nerve injury. Hyperalgesia and allodynia of the extremities often accompany this condition. Diagnosing and treating this disease is very complex. The Budapest criteria are currently the most widely accepted diagnostic criteria. Early diagnosis and treatment are essential for a favorable outcome in CRPS. Therapeutic modalities available for the treatment of CRPS include physical therapy, pharmacotherapy, and interventional techniques. Additional high-quality studies are needed to determine the best therapeutic option.
Keywords: complex regional pain syndrome; pain; chronic pain